The 1996 Sulawesi Tsunami - Pelinovsky, Efim; Hidayat, Rahman; Gegar Prasetya, Dede Yuliadi (1997)
On 1 January 1996 at 16.05 p.m. local time, an earthquake of magnitude M = 7.8 struck the central part of Sulawesi Island (Indonesia). It was accompanied by tsunami waves 2-4 m high. Nine people were killed and 63 were injured. A tsunami survey was conducted by Indonesian and Russian specialists. The measured tsunami runup heights and eyewitness accounts are reported and discussed. Historical data on the Sulawesi Island tsunamis are analysed and tsunami risk prediction in the central part of Sulawesi Island carried out for the first time. - Reproduced
Keywords: Field survey; Indonesia; Tsunami; Earthquake